Evaluating Gait and Locomotion in Rodents with the CatWalk. Issue 8 (9th August 2021) - Garrick, Jacqueline M.; Costa, Lucio G.; Cole, Toby B.; Marsillach, Judit
Abstract: Motor deficits can significantly affect the completion of daily life activities and have a negative impact on quality of life. Consequently, motor function is an important behavioral endpoint to measure for in vivo pathophysiologic studies in a variety of research areas, such as toxicant exposure, drug development, disease characterization, and transgenic phenotyping. Evaluation of motor function is also critical to the interpretation of cognitive behavioral assays, as many rely on intact motor abilities to derive meaningful data. As such, gait analysis is an important component of behavioral research and can be achieved by manual or video‐assisted methods. Manual gait analysis methods, however, are prone to observer bias and are unable to capture many critical parameters. In contrast, automated video‐assisted gait analysis can quickly and reliably assess gait and locomotor abnormalities that were previously difficult to collect manually. Here, we describe the evaluation of gait and locomotion in rodents using the automated Noldus CatWalk XT system. We include a step‐by‐step guide for running an experiment using the CatWalk XT system and discuss theory and considerations when evaluating rodent gait. The protocol and discussion provided here act as a supplemental resource to the manual for this commercially available system and can assist CatWalk users in their experimental design and implementation. © 2021 Wiley Periodicals LLC.